HUBUNGAN HIPERTENSI DENGAN FUNGSI KOGNITIF MENGGUNAKAN MINI MENTAL STATE PEMERIKSAAN (MMSE) PADA PASIEN RAWAT JALAN POLA INTERNA DI RSUD KOTA MAKASSAR - Andi Riska Gunawati; Andi Weri Sompa (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2018)
For knowing the relation of hypertension with cognitive function in outpatients interna poly in RSU D of Makassar City. Methods : This research type is analytic observational study with a cross sectional approach. The subjects in this study amounted to 60 respondents. The study was conducted in RSUD of Makassar City on 12th December 2014 until 27th January 2015. Samples were taken by purposive sampling. Data were obtained through direct interviews by using Mini Mental State Examination (MMSE) and physical examinations of blood pressure measurement. Data analysis was carried out in stages include univariate analysis, bivariate analysis by using Chi-square test on SPSS program. Results : The results of statistical tests by using chi-square indicate that there is relation of hypertension with cognitive function (p = 0,024; OR = 9,923 dan 95% CI =0,950 - 103,701). Beside it, there is also the relation of long history of hypertension with cognitive function (p = 0,000; OR = 39,000 dan 95% CI = 3,262 – 466,253). Conclusion : There is the relation of hypertension with cognitive function by using Mini Mental State Examination (MMSE). There is also the relation of long history of hypertension with cognitive function.